Digital Maslahah in Higher Education: Communicating Transformational Leadership through Implicit Islamic Ethics - Dhita Widya Putri; Aditya Nugroho Pratomo; Taufan Teguh Akbari (Jurnal Komunikasi Islam, 2025)
This research explores how university leaders employ transformational styles of Islamic leadership and migration ethics, and how such leaders in Islamic higher education navigate crisis. Using qualitative methods and a case study design, data were collected through semi-structured interviews with four strategic leaders from private universities in the Greater Jakarta Area. The findings demonstrate the emergence of "Digital Maslahah", a conception in which technology is used (though not only for operational efficiency) to sustain the ummah. In theory, this study proposes a new communication leadership theory that seeks to resolve the paradox of high-tech "digital infrastructure" and high-touch "humanist touch". This study proposes that the ability to convert and actualize the spiritual dimension of a leader to Miranda’s adaptive digital policies is the essential core of Islamic higher education.